PENGARUH MODEL PEMBELAJARAN SAVI BERBANTUAN VIDEO TERHADAP PRESTASI BELAJAR BAHASA INDONESIA SISWA KELAS V SDN DI GUGUS VII KOTA BENGKULU - Evitalia C. Aritonang; Nady Febri Ariffiando (JURIDIKDAS, 2023)
This study aims to analyze and determine the effect of the video-assisted SAVI learning model on the learning achievement of indonesian students of grade V SDN in cluster VII bengkulu city. This type of research is  a  quantitative  study  using quasi experimental method with the matching only pre-test and pos-test research design. The population of this study were all of class V at SDN Gugus VII with the status of a public school and having A accreditation. The sampling technique used cluster random sampling so that the VA class the from  SDN 49  consisted of 30 people as the experimental class and the VB class the from SDN 19 consisted of 26 people as the control class. The instrument used was written test sheet with data collection technique was in the form of pretest and posttest. Data analysis technique used quantitative analysis. The analysis result of post-test score showed significant difference between experimental class and the control class. The results of the research data were processed using a hypothesis test (t-test), namely the value of tcount (3.641) > ttable (1.670) so that Ha was accepted. Thus, it can be concluded that there is an influence of the video-assisted SAVI learning model on the learning achievement of Indonesian students of grade V SDN in Cluster VII, Bengkulu City.